ANALYSIS OF COMMUNITY SATISFACTION LEVELS WITH PUBLIC SERVICES BASED ON THE COMMUNITY SATISFACTION INDEX AT THE KARANG BEROMBAK URBAN VILLAGE OFFICE, WEST MEDAN SUBDISTRICT - Sisca Medania; Simon Patar Rizki Manalu; Hilman Lubis; Evalina Pakpahan (Yayasan Amanah Nur Aman, 2026)
Public service is a crucial aspect in realizing good governance. This study aims to analyze the level of public satisfaction with public services at the Karang Berombak Urban Village Office, West Medan Subdistrict, based on the Public Satisfaction Index (IKM) in accordance with PANRB Regulation No. 14 of 2017. This study used a descriptive quantitative approach with data collection using a questionnaire. A total of 100 respondents were selected using a purposive sampling technique. The results indicate that public services at the Karang Berombak Village Office are categorized as